2019
DOI: 10.1183/13993003.00800-2018
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and combined endosonographic staging of lung cancer (SCORE study)

Abstract: Guidelines recommend endosonography for mediastinal nodal staging in patients with resectable nonsmall cell lung cancer (NSCLC). We hypothesise that a systematic endobronchial ultrasound (EBUS) evaluation combined with an oesophageal investigation using the same EBUS bronchoscope (EUS-B) improves mediastinal nodal stagingversusthe current practice of targeted positron emission tomography (PET)-computed tomography (CT)-guided EBUS staging alone.A prospective, multicentre, international study (NCT02014324) was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 30 publications
0
57
0
Order By: Relevance
“…However, it should be considered that good overall accuracy does not necessarily correlate to high sensitivity. Earlier studies have used cut-off values varying from 5 to 10 mm with success [3][4][5][6][7][8]. Based on our results, we propose to at least routinely include nodes of ≥8 mm for aspiration when no additional predictive variables are used.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, it should be considered that good overall accuracy does not necessarily correlate to high sensitivity. Earlier studies have used cut-off values varying from 5 to 10 mm with success [3][4][5][6][7][8]. Based on our results, we propose to at least routinely include nodes of ≥8 mm for aspiration when no additional predictive variables are used.…”
Section: Discussionmentioning
confidence: 73%
“…However, there is no consensus on the lower limit in ultrasound size for aspiration. While the 10-mm short axis size, as equal to CT, is often used, cutoffs ranging from 5 to 10 mm are found across studies [3][4][5][6][7][8]. Studies assessing B-mode criteria such as node heterogeneity, shape, and a central hilar structure have also been found to be contradictory in their results [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that physicians did not consider adding EUS-B-FNA after systematic EBUS-TBNA to be useful in radiological N0 patients. A recent prospective study revealed that the addition of EUS-B-FNA was more valuable in terms of upstaging from single-level to multilevel N2/N3 disease, rather than upstaging from N0-1 to N2 disease [10]. We compared the diagnostic performance of endosonography based on tumor centrality and diameter; these two parameters were associated with the prevalence of occult mediastinal metastases [9,26,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…After systematic inspection of mediastinal, hilar, and interlobar lymph nodes (2R, 4R, 10R, 11R, 7, 11 L, 10 L, 4 L, 2 L, etc), nodal sampling was performed from N3 to N2, then to N1 when the short diameter of lymph node was 5 mm or more in sonography [10,11]. LN stations were determined based on the International Association for the Study of Lung Cancer LN map [12].…”
Section: Ebus-tbnamentioning
confidence: 99%
“…A combination of EUS‐B and EBUS improves in‐depth staging of lung cancer with better patient tolerance and access to evaluate upper paratracheal stations (2R and 2L), the left lower paratracheal station (4L) and possibly the left adrenal gland by a single operator during one session . A recent study demonstrated that combined endosonography showed an increased sensitivity of 9% for N2/N3 disease in lung cancer staging compared to conventional PET‐CT‐targeted EBUS . An extension to the assessment of structures located on both sides of the diaphragm has also been described previously .…”
Section: Discussionmentioning
confidence: 99%